2017
DOI: 10.1016/j.inffus.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble learning for data stream analysis: A survey

Abstract: In many applications of information systems learning algorithms have to act in dynamic environments where data are collected in the form of transient data streams. Compared to static data mining, processing streams imposes new computational requirements for algorithms to incrementally process incoming examples while using limited memory and time. Furthermore, due to the non-stationary characteristics of streaming data, prediction models are often also required to adapt to concept drifts. Out of several new pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
505
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 900 publications
(524 citation statements)
references
References 164 publications
(298 reference statements)
0
505
0
19
Order By: Relevance
“…The latter integrate several incremental single classifiers, and are often based on extending standard ensembles (like many variants of online bagging) or the weighted majority algorithm . Comprehensive reviews of various ensembles can be found in some recent surveys (Ditzler et al, 2015;Krawczyk et al, 2017). 6.3.…”
Section: Classification Of Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter integrate several incremental single classifiers, and are often based on extending standard ensembles (like many variants of online bagging) or the weighted majority algorithm . Comprehensive reviews of various ensembles can be found in some recent surveys (Ditzler et al, 2015;Krawczyk et al, 2017). 6.3.…”
Section: Classification Of Streamsmentioning
confidence: 99%
“…In recent years, class imbalances (also with variable class cardinalities or swapping roles of minority vs. majority classes) and detection of novel, appearing classes have been receiving increased interest (Sun et al, 2016). However, research on these topics is still in the early phase (Krawczyk et al, 2017).…”
Section: Classification Of Streamsmentioning
confidence: 99%
“…Detection of different types of shots is a special case of the concept drift detection in streams of data [17,28,41]. In the case of video signals, analyzed in this paper, detection of different types of shots requires development of special methods which account for different statistical properties of the video signals.…”
Section: Video Structure and Analysismentioning
confidence: 99%
“…Recently, these gained much attention among researchers. This new domain of data processing is analyzed, for instance, in the book by Gama [17] or in the papers by Krawczyk et al [28] or Woźniak et al [53], to name a few. The two domains-that is,streams of tensor data-were pioneered by the works by Sun et al [43,44], as will be further discussed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation